ANTI-HETEROGENEOUS NUCLEAR RIBONUCLEOPROTEIN B1 (ANTI-RA33) ANTIBODIES IN RHEUMATOID ARTHRITIS AND SYSTEMIC SCLEROSIS - P. A. Kuznetsova; A. L. Maslyansky; S. V. Lapin; O. Yu. Tkachenko; V. I. Mazurov (Научно-практическая ревматология)
Anti-heterogeneous nuclear ribonucleoprotein (RNP) autoantibodies (AAbs) are encountered in many autoimmune rheumatic diseases (ARDs). The potential diagnostic value of the RA33 AAb complex consisting of RNP A2 and alternative domains of the splicing proteins RNP B1 and RNP B2 is now of interest to rheumatologists. Subjects and methods. The authors studied the frequency of anti-RNP B1 AAbs in 300 patients with systemic ARDs, including those with rheumatoid arthritis (RA), ankylosing spondylitis (AS), systemic lupus erythematosus (SLE), systemic sclerosis (SSc), and Sjö gren's syndrome (SS) and in 53 people without ARDs, who constituted a control group. Serum anti-RNP B1 AAbs were assessed by enzyme immunoassay. Results and discussion. The frequency of anti-RNP B1 AAbs in patients with ARDs was much higher than that in the control group: 170/300 (56.6%) and 8/53 (13%) patients, respectively. Anti-RNP B1 AAbs were detected in 78.5% (113/144) of the patients with RA; 40.3% (23/57) of those with AS, in 67.5% (27/40) of those with SSc, in 36.4% (16/44) of those with SLE, and in 13.3% (2/15) of those with SS. The diagnostic sensitivity of the marker for RA was 78.5%, its diagnostic specificity was 84.9%; the likelihood ratio of positive and negative results was 5.24 and 0.24, respectively. In the patients with RA, the level of anti-RNP B1 AAbs significantly correlated with that of C-reactive protein and erythrocyte sedimentation rate, while in those with SSc the detection of anti-RNP B1 AAbs was related to the rigidity of the vascular wall and the presence of hypertension. The frequency of anti-RNP B1 AAbs among the RA patients seronegative for rheumatoid factor and anti-cyclic citrullinated peptide antibodies was 15.4%. Conclusion. Anti-RNP B1 AAs are a useful laboratory marker (with the upper limit of the normal range being 3.3 U/ml), but are of limited value in the diagnosis of RA. Anti-RNP B1 AAbs may be regarded as an additional diagnostic marker for RA.